(untitled) (Research, Society and Development, 2022)
Objective: to analyze the impact of the Covid-19 pandemic on the mental health of medical professionals in a public hospital in Teresina-PI. Methodology: cross-sectional, descriptive and quantitative study with strategic basics. The population object of the research was found by 29 physicians and a questionnaire with 10 questions was used for data collection, with the variables: gender, age, race, area of expertise in medicine and time, training in garments and undressing, previous diagnosis of insomnia, anxiety or depression, and treatment is performed using a 5-point scale to assess stressors, based on those most reported in the literature. Furthermore, scales were applied to screen for posttraumatic stress disorder (PC-PTSD), generalized anxiety disorder (GAD-2) and depression (PHO-2), validated in the literature. Results: 29 responses were collected, 10 female and 19 male. Most were between 20 and 30 years old (41.4%), working as a clinician (51.7%). 55% were screened positive for anxiety, 45% for post-traumatic disorder and 45% for depression. For stress control, regular physical activity and religion and/or spirituality (34.5%) were the oldest. The most prevalent stressors were having family members in the risk group and the lack of supplies and beds (75%). Conclusion: These results point to the need to implement effective mental health policies, in order to protect the old mental and physical well-being, as well as the permanence of quality to the population.